PHYSICAL AND CHEMICAL STABILITY TEST OF NEEM OIL CREAM (AZADIRACHTA INDICA) USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - SAPUTRI, FEBRINA AMELIA; HUSNI, PATIHUL; PUTRIANA, NORISCA ALIZA (International Journal of Applied Pharmaceutics, 2021)
Objective: This study aims to examine the physical and chemical stability of neem oil cream. Methods: Physical stability was conducted by storing the cream at room temperature (25±2 °C/65 %RH±5 %RH) and high temperature (40±2 °C/75 % RH±5 % RH) for 3 mo. HPLC method using Dionex with UV detection at 219 nm, Shodex (C-18) HPLC packed column (4.6 mmID x 250 mmL), acetonitrile: water [30:70] as mobile phase, 10 min isocratic elution with a flow rate of 1.0 ml/min with volume injection 20 μL was validated then was carried out to measure azadirachtin levels in neem oil cream. The chemical stability of azadirachtin in the cream was determined for 90 d by using this validated method. Results: The neem oil cream was physically stable. The HPLC method of azadirachtin meets all the validation parameters and can be used to analyze the chemical stability of azadirachtin in neem oil cream. Neem oil cream was stable for 4 w at 25 °C and for 1 w at 40 °C. Conclusion: The neem oil cream was either physically or chemically stable for 4 w at 25 oC and 1 w at 40 oC